1999
DOI: 10.1017/s0029665199000828
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid limitation regulates gene expression

Abstract: In mammals, the plasma concentration of amino acids is affected by nutritional or pathological conditions. For example, an alteration in the amino acid profile has been reported when there is a deficiency of any one or more of the essential amino acids, a dietary imbalance of amino acids, or an insufficient intake of protein. We examined the role of amino acid limitation in regulating mammalian gene expression. Depletion of arginine, cystine and all essential amino acids leads to induction of insulin-like grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 37 publications
2
21
1
1
Order By: Relevance
“…3A). This is contrary to the response detected for other genes regulated by depletion of essential AA, in that these genes can respond to single or complete AA deprivation (42,43). In fact, we know of no other gene regulated by AA deprivation that is not induced in response to complete AA depletion.…”
Section: Resultscontrasting
confidence: 76%
See 2 more Smart Citations
“…3A). This is contrary to the response detected for other genes regulated by depletion of essential AA, in that these genes can respond to single or complete AA deprivation (42,43). In fact, we know of no other gene regulated by AA deprivation that is not induced in response to complete AA depletion.…”
Section: Resultscontrasting
confidence: 76%
“…Our findings indicate that Gln is the only AA that, when added back to EBSS, is able to re-establish the induction of MnSOD mRNA levels. To further address the specificity of this response, we also evaluated asparagine synthetase (ASNS) (3,42,43), a gene known to be induced by both single and complete AA deprivation (Fig. 3, A and B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of other amino acid such as leucine have been associated with an increase in the synthesis and stability of mRNA for CHOP (37). This gene encodes a transcription factor that interacts with CCAAT/enhancer-binding proteins family, which in turn may inhibit the normal proliferation of cells (38). Therefore, essential amino acids appear to induce changes in T cells that ultimately inhibit their normal proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Various strategies have been proposed to treat obesity by promoting fat mobilization, increasing energy expenditure, and/or reducing food intake [1,7]. Accumulating evidence has shown that diets with higher protein and reduced carbohydrates are beneficial for weight loss and increase loss of body fat [8][9][10]. Because leucine can interact with the insulin-signaling pathway and appears to regulate the oxidative use of glucose by skeletal muscle through stimulation of glucose recycling via the glucose-alanine cycle, the key to understanding the relationship between dietary protein and carbohydrates is the relationship between the intake of leucine and glucose [11].…”
Section: Amino Acids and Obesitymentioning
confidence: 99%